Effects of mindful interpretation strategies on interpretation value-during-use and interpretation value-after-use. (September 2022) - Eck, Thomas; Ellis, Gary; Jiang, Jingxian
Abstract: This fully online study examined environmental interpretation narratives and tested their influence on participant's mindfulness and the value of their interpretive experiences. Dimensions of mindfulness were proposed to result from mindful interpretation strategies and a proposed model of interpretation value-during-use and interpretation value-after-use was explored. Four hundred fifty (450) participants were randomly assigned to participate in one of two brief mindfulness preparation conditions (Mindful Preparation- Present vs. Mindful Preparation- Absent), and then experience interpretation on one of two websites (Mindful Interpretation- Provided vs. Mindful Interpretation- Not Provided). Participants completed self-reported measures of mindfulness and its proposed outcomes immediately after visiting the website to which they were randomly assigned. Proposed outcomes were also tested, namely that mindfulness dimensions, immersion, and arousal would influence the participant's value-during-use. This in turn was thought to influence participant value-after-use, as measured by the variables learning, meaningfulness, memorability, delight, and intention to recommend. A-priori contrasts tested the differences among mindfulness dimension means, revealing a significant effect of mindful interpretation on one of the three dimensions of mindfulness: "noticing new things, sensitive to context." No other significant effects of mindful preparation or mindful interpretation were found. The value of participant interpretive experiences was also tested through a path model. Structural equation modeling (SEM) showed a very strong relationship between value-during-use and value-after-use (λ=.97). SEM and pooled confirmatory factor analysis revealed an acceptable model fit. Results suggest that mindful interpretation can positively influence visitor interpretive experiences, which in turn provides value during and after their experience. Management implications: Implementing Moscardo's (1996, 1999) suggestions to incorporate multisensory media, novelty, and questions in environmental interpretation was examined in this applied study. Means for mindfulness dimensions were mostly in the expected directions. Mindful interpretation techniques influenced one dimension of mindfulness. The partial support of Moscardo's models helped to identify what can enhance people's interpretive experiences. Implementing mindful interpretation narratives enhances content, would be low cost to implement, and can be monitored for efficacy. This study helped identify what interpretive experiences can address for visitors. Interpretation that is mindful can influence the value during and value after an interpretive experience.